GENESIS OF THE INSTITUTE FOR JUDICIAL DECISION REVISION IN CRIMINAL PROCEEDINGS (World Bulletin of Management and Law, 2024)
This article provides explanations on the role of judicial bodies in the system of state power in criminal justice, legal status, proceedings in criminal courts, the content and essence of the courts of first, appeal, Cassation, their activities, powers, reforms implemented and implemented in the judicial system.